Level of systolic blood pressure within the normal range and risk of cardiovascular events in the absence of risk factors in Chinese - Ji, Chunpeng; Wang, Na; Shi, Jihong; Huang, Zhe; Chen, Shuohua; Wang, Guodong; Wu, Shouling; Jonas, Jost B. (Journal of human hypertension, 2021)
The risk of cardiovascular disease (CVD) at currently defined normal systolic blood pressure (SBP) levels in individuals without CVD risk factors is not well examined. We evaluated whether higher systolic blood pressure within the range considered normal is associated with a higher CVD risk in Chinese without traditional CVD risk factors. The community-based study included 25,529 individuals (mean age:47.3 ± 12.3 years;range:18-95 years) with a baseline SBP of 90-129 mmHg, who were free of CVD and traditional CVD risk factors, and who were re-examined in biennial intervals. During a mean follow-up of 10.6 ± 1.49 years (maximum. 11.5 years), 847 CVD events occurred. CVD incidence per 1000 person-years increased with higher baseline SBP levels (SBP,90-99 mmHg:1.45;100-109 mmHg:2.15;110-119 mmHg:3.06; and 120-129 mmHg:3.80). After adjusting for CVD risk factors, the categorical Cox regression suggested that the CVD risk was not statistically significant for study participants with a baseline SBP level of 100-109 mmHg, 110-119 mmHg, and 120-129 mmHg compared with those with a baseline SBP level of 90-99 mmHg. If CVD risk factors including blood pressure categories which developed during follow-up were included in a time-dependent Cox regression analysis, the normal baseline SBP was still not associated with incident CVDs. A SBP between 90 and 129 mmHg was not associated with an increased CVD risk in a healthy population.